On protecting farmers’ new varieties: new approaches to rights on collective innovations in plant genetic resources - Salazar, Rene; Louwaars, Niels P.; Visser, Bert (International Food Policy Research Institute, 2006)
Current farmers’ breeding goes beyond the gradual selection in landraces, and includes development and maintenance of major new farmers’ varieties that are rather uniform, in particular in South-East Asia. Modern varieties developed in the formal sector have simply replaced landraces as the source of diversity, but have not abolished farmers’ breeding practices. Interpretations of the new international agreements on plant genetic resources should protect the development of modern farmers’ varieties. However, ensuring recognition of collective innovation, allowing access to relevant germplasm sources for farmers’ breeding activities, keeping materials freely available, and arranging for effective benefit sharing, all form major challenges. This paper proposes a new protective measure: namely “origin recognition rights.